Financial Performance Analysis Using the Economic Value Added Method - Indriakati, Andi Jenni (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This research aimed to evaluate the financial performance of cosmetics companies traded on the Indonesia Stock Exchange (IDX) using Economic Value Added (EVA) analysis. Research Design and Methodology: The study employed a descriptive-analytical approach, using audited financial statements from PT Mustika Ratu Tbk, PT Martina Berto Tbk, and PT Mandom Indonesia Tbk for the years 2017–2019. Quantitative data derived from secondary sources were analyzed using the EVA method to assess economic performance. Findings and Discussion: Results showed that PT Mustika Ratu Tbk and PT Martina Berto Tbk achieved positive EVA values, indicating favorable economic performance. In contrast, PT Mandom Indonesia Tbk had negative EVA values, reflecting financial difficulties. EVA analysis effectively distinguishes between successful and struggling companies. Implications: The findings offer valuable insights for investors and management to evaluate corporate performance using Economic Value Added (EVA). Companies with negative EVA values should enhance financial management. Future research may apply EVA to other industries or extend the study period.